2014
DOI: 10.1038/tpj.2014.73
|View full text |Cite
|
Sign up to set email alerts
|

Distinct gene expression profiles of proximal and distal colorectal cancer: implications for cytotoxic and targeted therapy

Abstract: Colorectal cancer (CRC) is a heterogeneous disease with genetic profiles and clinical outcomes dependent on the anatomic location of the primary tumor. How location impacts the molecular makeup of a tumor and how prognostic and predictive biomarkers differ between proximal versus distal colon cancers is not well established. We investigated the associations between tumor location, KRAS and BRAF mutation status, and the mRNA expression of proteins involved in major signaling pathways, including tumor growth (EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 70 publications
(62 reference statements)
4
26
1
1
Order By: Relevance
“…The study of Maus et al ,24 which is comparable to our study, revealed higher TS expression levels in rectal compared with distal colon cancer. Therefore, we searched for a possible association between DPYD variants and clinicopathological parameters.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study of Maus et al ,24 which is comparable to our study, revealed higher TS expression levels in rectal compared with distal colon cancer. Therefore, we searched for a possible association between DPYD variants and clinicopathological parameters.…”
Section: Discussionsupporting
confidence: 91%
“…To the best of our knowledge, these correlations have not been reported previously. However, polymorphisms and low mRNA expression of thymidylate synthase (TS), which is another enzyme with known impact on response and toxicity to 5-FU chemotherapy in patients with CRC,21–23 were found to be associated with mutant KRAS 24. This finding and our results point to a possible interaction between tumour-specific markers and host-specific factors.…”
Section: Discussionsupporting
confidence: 46%
“…Previous studies support the concept that primary tumor factors can drive prognosis after resection of metastatic 29 Of note, several investigators have reported on methylation differences across tumor sites and specifically that CpG island methylator phenotype is more common in RS CRC. 30,31 Conversely, CRC with a LS origin has been associated with higher levels of epiregulin and amphiregulin that, in turn, may confer a more indolent biologic behavior in KRAS tumors.…”
Section: Discussionmentioning
confidence: 94%
“…30,31 Conversely, CRC with a LS origin has been associated with higher levels of epiregulin and amphiregulin that, in turn, may confer a more indolent biologic behavior in KRAS tumors. 29 Several limitations should be considered when interpreting the data. As with all retrospective analyses, some bias likely occurred in the selection of patients for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is effective for patients in the early stages of this disease, but achieves poor outcomes for those with advanced cancer and microcarcinoma. With the development of molecular biology and related sciences, gene targeting therapy has become a research topic of significant interest in tumor treatment Maus et al, 2015). Gene targeting relies on the selection of a gene for treatment, therefore, the identification of a specific target affecting tumors is important.…”
Section: Introductionmentioning
confidence: 99%